MODULAÇÃO DA FOSFORILAÇÃO DE ERK E CREB POR GLUTAMATO E ÓXIDO NÍTRICO NA RETINA DE EMBRIÃO DE GALINHA - Magalhães, Cristiane Rosa (2009)
Glutamate is the major excitatory neurotransmitter in the central nervous system. Its actions are mediated by metabotropic or ionotropic receptors (iGluRs). iGluRs are largely expressed in the nervous system, and are present in the vertebrate retina. Recently, the activation of iGluRs has been associated to the activation of ERK pathway and CREB phosphorylation. In the chick embryo retina, the activation of NMDA receptors increases nitric oxide (NO) production, a neuroactive molecule often involved in glutamate actions. In the present work we have studied the effects of glutamate and NO on ERK and CREB phosphorylation in cultures of chick embryo retinal cells, or in the intact retina during development. Glutamate or the NO donor SNAP increased the phosphorylation levels of ERK2 and CREB in the cultures. Both the activation of ERK2 or CREB were dependent on PKG and Src kinase. CREB phosphorylation was dependent on ERK activation, and the glutamate effects were predominantly dependent on the activation of AMPA/Kainate iGluRs and NO production.. However, CREB activation was also dependent of different kinases such as PKA, PI3K and CAMK. We also showed that glutamateinduced CREB phosphorylation was restricted to the nuclei of glial cells in the cultures. In the 8-day-old (E8) chick embryo intact retina, NO induced the phosphorylation of ERK and CREB through the cGMP pathway but the phosphorylation of CREB was not dependent on ERK activation. Glutamate increased CREB phosphorylation in a dose-dependent manner. It was also observed that CREB phosphorylation was higher at E14 than in earlier retinas, and at this age CREB and ERK phosphorylation could be inhibited by NMDA or TrK receptor antagonists. The results reveal a complex chain of interactions involving glutamate receptors, NO production system, different kinases and neuronal-glial communication system.